Detection of iron deficiency anaemia by retic haemoglobin (ret-he) in haemodialysis patients on recombinant human erythropoietin (rHuEPO). - Ehram, Jamian (2010)
Iron deficiency anaemia (IDA) appears frequently in haemodialysis (HD) patients with rHuEPO (recombinant human erythropoietin) therapy. Iron deficiency is the most indices are inadequate to demonstrate the status or utility of iron in erythropoiesis. The aim of this study was to clarify the accuracy of RET-He in diagnosing IDA in haemodialysis patients with rHuEPO therapy compared with conventional iron parameters. Secondly to detect the changes in RET-He during iron supplementation for IDA patients, either this marker is a prospective and reliable indicator of iron sufficiency. A cross sectional study was done at HRPZ II from November 2008 to November 2009. 55 samples was collected and analysed for RET-He, ferritin and sTIR. RET-He was measured with the XE-2100 (Sysmex). Ferritin values were determined using ELISA method by AXSYM and sTfR by ELISA Biovender. Data were analyzed using SPSS software version 12.0. RET-He was significantly correlated with sTIR, MVC, MCH and TfR-F index 29.91+2.29 pg. Sensitivity and specificity of RET-He, 78.3% and 92 % respectively with AUC of 0.864. Percentage of IDA detected by RET-He was 63.64% but by sTfR and ferritin were 3.64% and 0% respectively. RET-He was significantly had aggrement with sTfR and TfR-F index, r= 0.042 and r=0.036 respectively, however no agreement with serum ferritin. To date detection rate of IDA in haemodialysis patients with rHuEPO by conventional method (sTfR & ferritin ) was low. However our current method by RET-He shows that it is a sensitive and specific marker of iron status in haemodialysis patients with rHuEPO. well as monitoring of responses to intravenous iron therapy in haemodialysis patients. xiii Thus we strongly suggest using RET-He as a diagnostic tool for the detection of IDA as A follow up To date detection rate of IDA in haemodialysis patients with rHuEPO by conventional method (sTfR & ferritin ) was low. However our current method by RET-He shows that it is a sensitive and specific marker of iron status in haemodialysis patients with rHuEPO. well as monitoring of responses to intravenous iron therapy in haemodialysis patients.